PROTOPOLITICAL DEMOCRACY AS THE POLITICAL INSTITUTION SPECIFICITY OF POST-SOVIET SPACE - Работягова, І.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The paper proposes the concept of „protopolitical democracy" as one that displays the prevalence of informalized political field before formalized, legal one. Key mechanisms of informalized adoption and implementation of government decisions that are traditional, protopolitical features of modern societies are identified. The degree of their influence on the political process of the post-Soviet states, including Ukraine is defined.